RHEED characterisation of the near surface microstructure of Ti-O based biocompatible coatings - Marlafeka, S.; Grant, D.M.; Brown, Paul D. (Institute of Physics Publishing, 2004)
Mechanically polished, annealed, nitric acid treated and aged in boiling water after nitriding, commercially pure Ti substrates have been characterised using reflection high-energy electron diffraction (RHEED) and secondary electron imaging, in terms of their naturally formed or ‘accelerated’ oxide layers. Annealing induced crystallisation and transformation of anatase to the rutile phase and led to increased roughness, with localised fracture and balling up of the surface oxide layer as the time and temperature of annealing were increased. Nitric acid modification produced no influence on the anatase to rutile transformation, whilst further aging in boiling water induced an acceleration of this transformation. RHEED data acquired at differing accelerating voltages have indicated a Ti-O phase gradation within annealed sol-gel derived V modified TiO2 layers deposited by spin coating onto Ti substrates.